The Effect of Tourist Satisfaction and Location on Decisions to Visit Tourist Attractions Wisata Wahana Surya Bengkulu - Afdhol Berkah Helandu; Yulius Wahyu Setiadi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of tourist satisfaction and location on the decision to visit Wahana Surya Bengkulu Tourism. This research is a type of quantitative research. Data collection techniques are interviews, observation, literature study and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results of the study are: Tourist satisfaction (X1) influences the decision to visit (Y) Wisata Wahana Surya Bengkulu with a tsig value of 0.000 thus Ho is rejected and Ha is accepted, which means that the variable X1 influences the decision to visit consumers (Y). Location (X2) influences the decision to visit (Y) Wisata Wahana Surya Bengkulu with a tsig value of 0.001, thus Ho is rejected and Ha is accepted, which means that the variable X2 influences the decision to visit (Y). Tourist satisfaction and location together influence the decision to visit with a Fsig value <α where the Fsig is 0.000.